Afro-futurism and the aesthetics of hope in Bekolo's Les Saignantes and Kahiu's Pumzi. Issue 2 (2nd July 2016) - Nyawalo, Mich
ABSTRACT: This article examines how both Bekolo and Kahiu deploy afrofuturist aesthetics in their films Les Saignantes and Pumzi in order to critique afro-pessimist perspectives from which socio-economic realities on the continent are often framed. Les Saignantes confronts the viewer with a question: "How can you make an anticipation [or futuristic] film in a country that has no future?" It is therefore by juxtaposing political realities against the narrative and aesthetic conventions of film genres that Bekolo seeks to interrogate the seemingly immutable perspectives from which African realities are examined or perceived. Both Bekolo and Kahiu's films are set in dystopic futures. Kahiu's film, Pumzi, seeks to question the fatality of present African realities by engaging dystopian politics. It is ultimately through the aesthetics of afro-futurism that both films manage to critique dominant ways of conceiving the African present by setting their works in alternative futures.